2020
DOI: 10.20944/preprints202011.0586.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Compositions and Antioxidant Activities of Indonesian Citrus Essential Oils and Their Elucidation Using Principal Component Analysis

Abstract: Citrus essential oils (EOs) have various bioactivities like antioxidants, with many applications. Antioxidant activities depend on the chemical compositions of the EOs, which are affected by climate, soil, and geographical region. Thus, investigations on chemical compositions and antioxidant activities of Citrus EOs in different countries are valuable. In this study, we distilled EOs from peels of Indonesian-grown Citrus, including C. nobilis, C. limon, C. aurantifolia, C. amblycarpa, and Citrus spp.Chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Oliveira et al (2015) reported that p-Cymene has antioxidant potential and can act as a neuroprotective agent in the brain. This is also supported by Julaeha et al (2020), who reported that p-Cymene and o-Cymene are responsible for the antioxidant activity of C. limon EO. At RT 6.284, cis-p-Menth-2,8-dienol, which has anticancer, antimicrobial, and antitumor potential (Nayak et al, 2014), was found after treatment with T1 (4.74%), T11 (5.28%), and T12 (5.36%).…”
Section: /10supporting
confidence: 68%
“…Oliveira et al (2015) reported that p-Cymene has antioxidant potential and can act as a neuroprotective agent in the brain. This is also supported by Julaeha et al (2020), who reported that p-Cymene and o-Cymene are responsible for the antioxidant activity of C. limon EO. At RT 6.284, cis-p-Menth-2,8-dienol, which has anticancer, antimicrobial, and antitumor potential (Nayak et al, 2014), was found after treatment with T1 (4.74%), T11 (5.28%), and T12 (5.36%).…”
Section: /10supporting
confidence: 68%
“…This result was in a comparable range with previously reported studies. The extraction yield of orange peel EOs was 3.15% in the study of Gursoy, Tepe, and Sokmen (2010), whereas another study obtained the higher extraction efficiency of 3.7% (Julaeha et al, 2020). The variation of EOs in the orange peel could be ascribed to the differences in genetic (Farhat et al, 2011;Julaeha et al, 2020;Okunowo et al, 2013;Singh et al, 2010).…”
Section: Characterization Of Orange Peel Essential Oilsmentioning
confidence: 81%
“…The extraction yield of orange peel EOs was 3.15% in the study of Gursoy, Tepe, and Sokmen (2010), whereas another study obtained the higher extraction efficiency of 3.7% (Julaeha et al, 2020). The variation of EOs in the orange peel could be ascribed to the differences in genetic (Farhat et al, 2011;Julaeha et al, 2020;Okunowo et al, 2013;Singh et al, 2010). This result indicated that the orange peels could be a feasible and applicable source for EOs production due to higher extraction yield compared to others.…”
Section: Characterization Of Orange Peel Essential Oilsmentioning
confidence: 83%
“…Other compounds at lower concentrations in the EO of M. floribunda, such as o -cymene, γ-terpinene, α-terpineol, myrcene, and α-pinene, also have antioxidant potential [ 147 , 148 , 149 , 150 , 151 ]. The synergistic and/or antagonistic effects of the constituents of this EO may explain its high capture of free radicals considering that the volatile components in the sample are known for their excellent antioxidant properties [ 152 , 153 ].…”
Section: Resultsmentioning
confidence: 99%